Quality Analysis of Service "One Kecamatan One Center of Entrepreneurship" (OK OCE) in East Jakarta - Noer Wachid; Retnowati WD Tuti (Journal of Governance and Public Policy, 2020)
In August 2018 DKI Jakarta Province recorded an unemployment rate which decreased by 6.24 percent from the previous March 2017 of 7.14%. The proportion of workers with worker/employee status has decreased while the status of self-employed has increased. The increasing percentage of self-employed people indicates that the interest in entrepreneurship in the population of DKI Jakarta has increased, in line with the intense socialization of the Integrated Entrepreneurship Development program that began with a community movement called OK OCE. The purpose of this study is to analyze the quality of Integrated Entrepreneurship Development services in the Cooperative Micro Small Medium Enterprises (CMSME) Implementing Unit in Jatinegara District and determine what factors affect the quality of Integrated Entrepreneurship Development services. This research uses a descriptive method with a qualitative approach, this research was conducted by observation, interview, and documentation techniques. The theory used in this study is the theory of Zeithaml (1990) with 5 indicators of service quality measurement, namely tangible dimensions, reliability, responsiveness, assurance, and empathy. Every dimension has indicators to measure service quality. In this study, triangulation was used to check the validity of the research data. The results showed that the Integrated Entrepreneurship Development service quality of the five dimensions measured was still relatively Good.